Conversions of parts per million on soil test reports to pounds per acre - Guodong Liu; Yuncong Li; Aparna Gazula (EDIS)
December 18th, 2013 Soil testing and the resulting fertilization recommendations are critical for appropriate nutrient management in commercial vegetable production, but growers and soil experts sometimes speak different languages. This 8-page fact sheet provides a simple conversion method for crop consultants, crop advisors, growers, students, and researchers who are interested in nutrient and water management of crop production. Written by Guodong Liu, Yuncong Li, and Aparna Gazula, and published by the UF Department of Horticultural Sciences, August 2013.